Case Report: A Recovered SARS CoV-2 Patient Protected From Reinfection - Mahallawi, Waleed (Frontiers in Medicine, 2020)
The COVID-19 pandemic caused by SARS CoV-2 is a worldwide emergency, and is taking a substantial toll on human health, lives, and the global economy. Due to the novelty of this virus, no SARS CoV-2-specific treatments or licensed vaccines are available though few vaccines are undergoing clinical trials. Therefore, continued research into an effective vaccine is an urgent necessity. The reinfection of recovered patients is one of the major concerns of healthcare providers worldwide. Health authorities are currently seeking evidence of protection from reinfection in recovered individuals. This is the first case report in Saudi Arabia on a patient who was diagnosed as COVID-19-positive; recovered; and after successful recovery was protected against reinfection.